2014
DOI: 10.1016/j.ecoenv.2014.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectivity in bioaccumulation and excretion of epoxiconazole by mealworm beetle (Tenebrio molitor) larvae

Abstract: a b s t r a c tStereoselectivity in bioaccumulation and excretion of stereoisomers of epoxiconazole by mealworm beetle (Tenebrio molitor) larvae through dietary exposure was investigated. Liquid chromatography tandem mass spectrometry (HPLC À MS/MS) method that use a ChiralcelOD-3R[cellulosetris-Tris-(3, 5-dichlorophenyl-carbamate)] chromatography column was applied to carry out chiral separation of the stereoisomers. Wheat bran was spiked with racemic epoxiconazole at two dose levels of 20 mg/kg and 2 mg/kg (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…However, this reported correlation could not be readily identified from the data presented in that publication. Several other studies on chiral fungicides showed that T. molitor larvae metabolized and degraded the fungicides epoxiconazole (log K ow 3.58) (Lv et al., ), metalaxyl (log K ow 1.65) (Gao et al., ), benalaxyl (log K ow 3.67) (Gao et al., ), and mycolobutanil (log K ow 2.94) (Lv et al., ). These experimental results all are consistent with the K ow pattern observed by Houbraken et al.…”
Section: Chemical Hazardsmentioning
confidence: 99%
“…However, this reported correlation could not be readily identified from the data presented in that publication. Several other studies on chiral fungicides showed that T. molitor larvae metabolized and degraded the fungicides epoxiconazole (log K ow 3.58) (Lv et al., ), metalaxyl (log K ow 1.65) (Gao et al., ), benalaxyl (log K ow 3.67) (Gao et al., ), and mycolobutanil (log K ow 2.94) (Lv et al., ). These experimental results all are consistent with the K ow pattern observed by Houbraken et al.…”
Section: Chemical Hazardsmentioning
confidence: 99%
“…This suggests the existence of many pesticide exposure pathways and a high likelihood that pesticide residues are present in mealworms from various feed sources. In controlled studies, pesticides were detected and bioaccumulated in mealworms after they consumed residue-treated crops [10,11]. It is also possible to intentionally spray chemicals on insect farms for pest control [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, simultaneous analysis of pesticide multiresidues in edible insects is needed to understand pesticide residue patterns and to rapidly monitor samples obtained from controlled studies or commercial insect farms. In mealworm samples, there have been no reports related to pesticide multiresidue analysis, and only a few studies covering a small number of pesticides have been published [10,11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In literature on the effects of reared insects discussed in a previous review (Van der Fels-Klerx et al, 2018), it was largely concluded that tested pesticides did not accumulate in the considered species. These included azoxystrobin and propiconazole (Lalander et al, 2016), chlorpyrifos and chlorpyrifos-methyl, and pirimiphos-methyl (Purschke et al, 2017) in H. illucens larvae, and epoxiconazole (Lv et al, 2014), metalaxyl (Gao et al, 2014), benalaxyl (Gao et al, 2013), and mycolobutanil (Lv et al, 2013) in A. diaperinus larvae. In addition, Poma and co-authors (Poma et al, 2017) confirmed the presence of pirimiphos-methyl in Locusta migratoria and in some insect products including a Buggie burger.…”
Section: Pesticidesmentioning
confidence: 99%